Singular and Combined Effects of Essential Oil and Honey of Eucalyptus Globulus on Anti-Inflammatory, Antioxidant, Dermatoprotective, and Antimicrobial Properties: In Vitro and In Vivo Findings - Hamza M. Assaggaf; Hanae Naceiri Mrabti; Bodour S. Rajab; Ammar A. Attar; Munerah Hamed; Ryan A. Sheikh; Nasreddine El Omari; Naoual El Menyiy; Omar Belmehdi; Shafi Mahmud; Mohammed Merae Alshahrani; Moon Nyeo Park; et al. (Molecules, 2022)
Eucalyptus globulus is a plant widely used by the world population, including Morocco, in the treatment of several pathologies. The aim of this work is to evaluate the antioxidant, anti-inflammatory, dermatoprotective, and antimicrobial effects of essential oil and honey from E. globulus, as well as their combination. Chemical composition was determined by GC-MS analysis. The antioxidant activity was evaluated by three tests, namely, DPPH, reducing power, and the β-carotene/linoleic acid assay. The anti-inflammatory activity was investigated in vitro (5-lipoxygenase inhibition) and in vivo (carrageenan-induced paw edema model), while the dermatoprotective activity was tested in vitro (tyrosinase inhibition). Moreover, the antibacterial activity was assessed using agar well diffusion and microdilution methods. The results showed that eucalyptol presents the main compound of the essential oil of E. globulus (90.14%). The mixture of essential oil with honey showed the best antioxidant effects for all the tests used (0.07 < IC50 < 0.19 mg/mL), while the essential oil was the most active against tyrosinase (IC50 = 38.21 ± 0.13 μg/mL) and 5-lipoxygenase (IC50 = 0.88 ± 0.01 μg/mL), which corroborated the in vivo test. Additionally, the essential oil showed the best bactericidal effects against all strains tested, with inhibition diameter values ranging from 12.8 to 21.6 mm. The findings of this work showed that the combination of the essential oil with honey showed important results in terms of biological activity, but the determination of the underlying mechanisms of action remains a major prospect to be determined.